Macrophages promote cartilage regeneration in a time‐ and phenotype‐dependent manner. Issue 4 (11th February 2022) - Yang, Jiabei; Zhang, Xuewei; Chen, Jiaqing; Heng, Boon Chin; Jiang, Yangzi; Hu, Xiaoyu; Ge, Zigang
Abstract: Immune regulation of osteochondral defect regeneration has not yet been rigorously characterized. Although macrophages have been demonstrated to regulate the regeneration process in various tissues, their direct contribution to cartilage regeneration remains to be investigated, particularly the functions of polarized macrophage subpopulations. In this study, we investigated the origins and functions of macrophages during healing of osteochondral injury in the murine model. Upon osteochondral injury, joint macrophages are predominantly derived from circulating monocytes. Macrophages are essential for spontaneous cartilage regeneration in juvenile C57BL/6 mice, by modulating proliferation and apoptosis around the injury site. Exogeneous macrophages also exhibit therapeutic potential in promoting cartilage regeneration in adult mice with poor regenerative capacity, possibly via regulation of PDGFRα + stem cells, with this process being influenced by initial phenotype and administration timing. Only M2c macrophages are able to promote regeneration of both cartilage tissues and subchondral bone. Overall, we reveal the direct link between macrophages and osteochondral regeneration and highlight the key roles of relevant immunological niches in successful regeneration. Abstract : Upon acute cartilage injury, circulating monocytes infiltrate into the injured joint, regulated by CCR2, and constitute the majority of macrophage population in synovium. Macrophages and stem cells exhibit colocalized distribution in synovium and the defect area. Macrophage depletion reduced synovium hyperplasia and hampered cartilage regeneration. M2c macrophages injected at 2 weeks after injury enhanced cartilage and subchondral bone regeneration, potentially by regulating stem cells. Extended synovium tissues could be a potential approach for cells to migrate to the defect area.